Initial dual oral combination therapy in pulmonary arterial hypertension. Issue 6 (17th March 2016) - Sitbon, Olivier; Sattler, Caroline; Bertoletti, Laurent; Savale, Laurent; Cottin, Vincent; Jaïs, Xavier; De Groote, Pascal; Chaouat, Ari; Chabannes, Céline; Bergot, Emmanuel; Bouvaist, Hélène; Dauphin, Claire; et al.
Treatment for pulmonary arterial hypertension (PAH) has been underpinned by single-agent therapy to which concomitant drugs are added sequentially when pre-defined treatment goals are not met. This retrospective analysis of real-world clinical data in 97 patients with newly diagnosed PAH (86% in New York Heart Association functional class III−IV) explored initial dual oral combination treatment with bosentan plus sildenafil (n=61), bosentan plus tadalafil (n=17), ambrisentan plus tadalafil (n=11) or ambrisentan plus sildenafil (n=8). All regimens were associated with significant improvements in functional class, exercise capacity, dyspnoea and haemodynamic indices after 4 months of therapy. Over a median follow-up period of 30 months, 75 (82%) patients were still alive, 53 (71%) of whom received only dual oral combination therapy. Overall survival rates were 97%, 94% and 83% at 1, 2 and 3 years, respectively, and 96%, 94% and 84%, respectively, for the patients with idiopathic PAH, heritable PAH and anorexigen-induced PAH. Expected survival rates calculated from the French equation for the latter were 86%, 75% and 66% at 1, 2 and 3 years, respectively. Initial combination of oral PAH-targeted medications may offer clinical benefits, especially in PAH patients with severe haemodynamic impairment. Initial dual combination therapy may offer potential benefits in PAH patients with severe haemodynamic impairment http://ow.ly/YNxgk